High-dose intravenous epoetin does not increase blood pressure in critically ill patients with acute kidney injury - Md Ralib, Azrina (Dustri-Verlag, 2013)
Treatment of renal anemia with erythropoietic stimulating agents sometimes increases blood pressure. It is uncertain whether this is due to direct vasoconstriction and/or increased red blood cell mass. We conducted a post-hoc analysis of 160 critically ill patients in the EARLYARF trial with elevated urinary γ-glutamyltranspeptidase and alkaline phosphatase, indicating acute kidney injury. Patients received two doses of intravenous epoetin (500 U/kg), 24 hours apart, or placebo, in a randomized, double-blind study design. Hourly mean arterial pressure (MAP), and norepinephrine equivalent dose (NED: determined using equipotency conversion factors for doses of epinephrine, vasopressin, phenlyephrine, or dopamine) were extracted from clinical records. The differences between baseline and maximum MAP and NED (∆MAP and ∆NED) over 4, 24, 72-hour, and 30-day periods following study drug administration were compared between groups. At baseline, MAP was 78±14 mmHg in the epoetin group and 81±15 mmHg in the placebo group (p=0.22). There were no differences between groups in ∆MAP (6±14 versus 7±14 mmHg; p=0.53), in ∆NED, or in ∆MAP adjusted for ∆NED at 4 hours, or at any time points. A subgroup analysis of only those patients not requiring vasopressor support (n=71) also showed no differences between epoetin and placebo for all outcomes. We concluded that intravenous high dose epoetin does not acutely increase blood pressure, suggesting no acute vasoconstrictor effect in this setting.